Robot-assisted laparoscopic partial hepatic caudate lobectomy. Issue 5 (3rd September 2019) - Chen, Jian-Cong; Huang, Chun-Yu; Wang, Jun-Cheng; Zhang, Yao-Jun; Xu, Li; Chen, Min-Shan; Zhou, Zhong-Guo
Abstract: Background: Hepatic caudate lobectomy is considered to be a technically difficult surgery because of the unique anatomy and deep location of the hepatic caudate lobe. Here, we assessed the technical feasibility and safety of robotic partial caudate lobectomy using the da Vinci ® Surgical System and compared it with traditional open/laparoscopic surgery. Material and methods: Six patients diagnosed with liver cancer (primary liver cancer, 5; metastasis of breast cancer, 1) who underwent caudate lobectomy were prospectively enrolled. Two patients underwent robotic surgery, one underwent laparoscopic surgery, and three underwent traditional/open surgery. Surgical procedure, recovery, and characteristics of robotic surgery were noted and compared with other approaches. Results: All surgeries were successfully completed, and no serious postsurgical complications were observed. In the robotic group, the time taken to complete the surgery and the estimated intraoperative bleeding were 150 and 90 min and 50 and 100 ml in patient 1 and patient 2, respectively. The patients were able to tolerate fluid diet on the following postsurgical day. These two patients had no postsurgical complications and were discharged from the hospital on days 5 and 6 after recovery, respectively. Pathologically, the margins of specimens obtained from these two patients were tumor-free (R0 resection). Tumor size in the traditional/open group was larger than that in the robotic and laparoscopic groups. Blood loss in the laparoscopic case was 50 ml and was less than that in the traditional/open surgery cases (300, 2100, and 1500 ml). Conclusions: Robot-assisted partial hepatic caudate lobectomy is a technically feasible surgery. Our study illustrated an advantage of robotic hepatic caudate lobectomy over laparoscopic or traditional/open surgery and suggested that da Vinci ® minimally invasive hepatectomy is applicable in even more technically challenging anatomic locations.